Coronaviruses Research in BRICS Countries - Fielding, Burtram C.; Schäfer, Georgia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
SARS-CoV-2 has infected more than 105 million people worldwide. During this pandemic, researchers and clinicians have been working to understand the molecular mechanisms that underpin viral pathogenesis by studying viral-host interactions. Now, with the global rollout of various COVID-19 vaccines-based on the neutralization of the spike protein using different technologies-viral immunology and cell-based immunity are being investigated. Researchers are also studying how various SARS-CoV-2 genetic mutations will impact the efficacy of these COVID-19 vaccines. At the same time, various antiviral drugs have been identified or repurposed that have potential as anti-SARS-CoV-2 treatments. BRICS (Brazil, Russia, India, China, and South Africa) is the acronym used to associate five major emerging national economies. The BRICS countries are known for their significant influence on regional affairs, including being leaders in scientific and clinical research and innovation. This Special Issue includes researchers from BRICS countries, in particular South Africa, involved in the study of SARS-CoV-2 and COVID-19. Original articles, as well as new perspectives or reviews on the matter, were welcomed. Research in the fields of vaccine studies, pathogenesis, genetic mutations, viral immunology, and antiviral drugs were especially encouraged.